Scanning Electron Microscopy (SEM) Evaluation of the Ultrastructural Effects on Conjunctival Epithelial Cells of a New Multiple-Action Artificial Tear Containing Cross-Linked Hyaluronic Acid, Cationic Liposomes and Trehalose - Troisi, Mario; Del Prete, Salvatore; Troisi, Salvatore; Marasco, Daniela; Rinaldi, Michele; Costagliola, Ciro (Biomedicines, 2024)
The authors performed an ex vivo and in vivo evaluation of the ultrastructural effects on the conjunctival epithelial cells of a new multiple-action tear substitute containing cross-linked hyaluronic acid, lipids and trehalose (Trimix®), using scanning electron microscopy (SEM) with conjunctival impression cytology. The ex vivo study highlights the persistence and distribution of the product at 5 and 60 min on a monolayer of conjunctival epithelial cells and an increase in microvilli density at the 60 min evaluation. In vivo examination was conducted on three subjects with different grades of ocular surface inflammation, treated with one drop of the product twice daily for thirty days. At the baseline (T0) and twelve hours after the last administration of the tear drop (T30), impression cytology of the upper bulbar conjunctiva for SEM evaluation of conjunctival epithelial cells was carried out. Slit lamp examination (SLE), corneal and conjunctival Fluotest, tear film break-up time (TBUT), and ocular surface disease index (OSDI) questionnaires were also performed to correlate the ultrastructural results with the clinical findings. After 30 days of treatment, a significant improvement in all clinical and symptomatic parameters and in the condition of the ocular surface was detected, with microvillar regeneration and strengthening in all the patients, and a complete restoration in 2/3 of them. The persistence and distribution of the product on the epithelial cells was also noted 12 h after the last administration. The results, therefore, suggest a marked epitheliotropic effect along with a high residence time of the tear substitute.